A Comprehensive Brownian Dynamics-Based Forward Model for Analytical (Ultra)Centrifugation - Thajudeen, Thaseem; Walter, Johannes; Uttinger, Maximilian; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2017)
In this study, it is demonstrated how Brownian dynamics (BD) simulations can be used as a comprehensive forward model for analytical ultracentrifugation (AUC) and analytical centrifugation experiments. BD simulations are a versatile alternative to the numerical solution of Lamm's equation. Time dependent concentration profiles can be accurately predicted by means of the BD simulations even for colloidal systems with multiple species. It is shown that in combination with Mie's theory for light scattering, BD simulations can be extended to generate data mimicking a multiwavelength detector for AUC. The forward model can be utilized as a comprehensive tool for developing and testing sophisticated data analyzing tools that can enhance the capabilities of using centrifugation-based techniques for characterizing nanoparticles. The model is validated using common analysis tools developed for the evaluation of sedimentation velocity data generated by a single wavelength extinction detector. The accuracy of the code is also proved using the recently developed and highly versatile High Dynamic Range-MULTIwavelength FITting tool for accurately predicting particle size distributions via gravitational sweep experiments performed in AUCs equipped with multiwavelength detectors.
Keywords: Brownian dynamics; analytical ultracentrifugation; Mie scattering; extinction coefficient; multiwavelength detectors

A widely applicable method to stabilize nanoparticles comprising oxygen-rich functional groups - Distaso, Monica; Lautenbach, Vanessa; Uttinger, Maximilian; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Peukert, Wolfgang (Powder Technology, 2022)
Colloidal stability of nanoparticle suspensions is fundamental to apply nanomaterials in functional devices and to develop new methodologies in nanoscience. Herein, a versatile method is described to disperse and stabilize various solids with technological applications in pharmaceutical industry, batteries and fuel cells, dye sensitized solar cells, pigments and coatings. The method is based on the use of Zr(IV) hydroxo-complexes that interact with carboxylic- and hydroxo- functional groups at the solid-liquid interfaces of active pharmaceutical ingredients (API), carbon black (CB) and Pt-CB, metal oxide and metal oxy-hydroxide nanoparticles. The colloidal stability is assessed via sedimentation analysis, electrophoretic measurements, ultraviolet-visible spectroscopy (UV–Vis), attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) and isothermal titration calorimetry (ITC). The effect of the anion and pH are studied in depth. Finally, the current work enables liquid phase length and diameter characterization of rod-like goethite (α-FeOOH) particles without relying on tedius counting the particles from electron micrographs.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Functional devices; Nanoparticles; Nanoparticulate inks; Stability; Surface

Brownian dynamics simulations of analytical ultracentrifugation experiments exhibiting hydrodynamic and thermodynamic non-ideality - Uttinger, Maximilian; Walter, Johannes; Thajudeen, Thaseem; Wawra, Simon; Peukert, Wolfgang (Nanoscale, 2017)

Determination of the Lateral Dimension of Graphene Oxide Nanosheets Using Analytical Ultracentrifugation - Walter, Johannes; Nacken, Thomas; Damm, Cornelia; Thajudeen, Thaseem; Eigler, Siegfried; Peukert, Wolfgang (Small, 2014)
In this paper, a method to determine the lateral dimensions of 2D nanosheets directly in suspension by analytical ultracentrifugation (AUC) is shown. The basis for this study is a well-characterized and stable dispersion of graphene oxide (GO) monolayers in water. A methodology is developed to correlate the sedimentation coefficient distribution measured by AUC with the lateral size distribution of the 2D GO nanosheets obtained from atomic force microscopy (AFM). A very high accuracy can be obtained by virtue of counting several thousand sheets, thereby minimizing any coating effects or statistical uncertainties. The AFM statistics are further used to fit the lateral size distribution obtained from the AUC to determine the unknown hydrodynamic sheet thickness or density. It is found that AUC can derive nanosheet diameter distributions with a relative error of the mean sheet diameter of just 0.25% as compared to the AFM analysis for 90 mass% of the particles in the distribution. The standard deviation of the size-dependent error for the total distribution is found to be 3.25%. Based on these considerations, an expression is given to calculate the cut size of 2D nanosheets in preparative centrifugation experiments.

Determination of the length and diameter of nanorods by a combination of analytical ultracentrifugation and scanning mobility particle sizer - Thajudeen, Thaseem; Walter, Johannes; Srikantharajah, Rubitha; Lübbert, Christian; Peukert, Wolfgang (Nanoscale Horizons, 2017)
A combination of orthogonal measurement techniques is utilized in this study to predict the average lengths and diameters of colloidal nanorods. Sedimentation coefficient distributions and electrical mobility distributions obtained from analytical ultracentrifugation and a scanning mobility particle sizer, respectively, are used for the hydrodynamic correlation. The method is validated theoretically and application to Au and ZnO nanorod samples is shown. The results demonstrate that the combination of both measurement techniques is an excellent method for the two-dimensional characterization of nanorods.

Determination of the two-dimensional distributions of gold nanorods by multiwavelength analytical ultracentrifugation - Wawra, Simon; Pflug, Lukas; Thajudeen, Thaseem; Kryschi, Carola; Stingl, Michael; Peukert, Wolfgang (Nature Communications, 2018)
Properties of nanoparticles are influenced by various parameters like size, shape or composition. Comprehensive high throughput characterization techniques are urgently needed to improve synthesis, scale up to production and make way for new applications of multidimensional particulate systems. In this study, we present a method for measuring two-dimensional size distributions of plasmonic nanorods in a single experiment. Analytical ultracentrifuge equipped with a multiwavelength extinction detector is used to record the optical and sedimentation properties of gold nanorods simultaneously. A combination of sedimentation and extinction properties, both depending on diameter and length of the dispersed nanorods, is used to measure two-dimensional distributions of gold nanorod samples. The length, diameter, aspect ratio, volume, surface and cross-sectional distributions can be readily obtained from these results. As the technique can be extended to other non-spherical plasmonic particles and can be used for determining relative amounts of particles of different shapes it provides complete and quantitative insights into particulate systems.
EAM Import::2019-03-13

Enhanced Crystallization of Lysozyme Mediated by the Aggregation of Inorganic Seed Particles - Weichsel, Ulrike; Segets, Doris; Thajudeen, Thaseem; Maier, Eva-Maria; Peukert, Wolfgang (Crystal Growth and Design, 2017)
We show that aggregation plays a major role in seeded growth of protein crystals. The seeded batch approach provides the opportunity to set the starting conditions for protein crystallization by adding a defined amount of well-characterized seed particles. The experimental observations for tetragonal hen egg-white lysozyme (LSZ) confirm the concept of the oriented aggregation of larger building blocks to form a protein crystal. It was shown that the aggregation of the seed particles/bioconjugates is advantageous for the product quality in terms of larger and more defined LSZ crystals and in terms of accelerated reaction kinetics. We present a population balance (PB) model for the seeded batch crystallization of LSZ considering the aggregation of growth units to form protein crystals. For the modeling of crystal growth, evolving particle size distributions (PSDs) of agglomerating LSZ molecules were measured by dynamic light scattering (DLS). Moreover, the aggregation of seed particles in LSZ solutions under crystallization conditions was investigated by DLS. In line with our expectations, the number of seeds was found to be important as it strongly affects the collision frequency in the aggregation term of our PB model. Finally, the applied model gives trends of the supersaturation depletion curves and orders of magnitude of the measured CSDs in particle size correctly, ranging from only a few nanometers up to micrometer-sized particles/crystals. Thus, by the combination of PB modeling and experimentally determined crystallization parameters, insights into the crystal formation mechanism were obtained. To the best of our knowledge, this is the first attempt to model growth within a crystal population by an aggregation mechanism induced by seeding with foreign particles.

Ionomer and protein size analysis by analytical ultracentrifugation and electrospray scanning mobility particle sizer - Wawra, Simon; Thoma, Martin; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Damm, Cornelia; Peukert, Wolfgang (European Biophysics Journal, 2018)
Keywords: Analytical ultracentrifugation; Scanning mobility particle sizer; Combined analysis; Multiwavelength detector

Multidimensional Nanoparticle Characterization by Means of Analytical Ultracentrifugation and Multiwavelength Detection - Peukert, Wolfgang; Nacken, Thomas; Walter, Johannes; Thajudeen, Thaseem; Segets, Doris; Sherwood, Peter; Stafford, Walter (Chemie Ingenieur Technik, 2016)
Keywords: Nanoparticle; centrifugation

New possibilities of accurate particle characterisation by applying direct boundary models to analytical centrifugation - Walter, Johannes; Thajudeen, Thaseem; Süß, Sebastian; Segets, Doris; Peukert, Wolfgang (Nanoscale, 2015)
Analytical centrifugation (AC) is a powerful technique for the characterisation of nanoparticles in colloidal systems. As a direct and absolute technique it requires no calibration or measurements of standards. Moreover, it offers simple experimental design and handling, high sample throughput as well as moderate investment costs. However, the full potential of AC for nanoparticle size analysis requires the development of powerful data analysis techniques. In this study we show how the application of direct boundary models to AC data opens up new possibilities in particle characterisation. An accurate analysis method, successfully applied to sedimentation data obtained by analytical ultracentrifugation (AUC) in the past, was used for the first time in analysing AC data. Unlike traditional data evaluation routines for AC using a designated number of radial positions or scans, direct boundary models consider the complete sedimentation boundary, which results in significantly better statistics. We demonstrate that meniscus fitting, as well as the correction of radius and time invariant noise significantly improves the signal-to-noise ratio and prevents the occurrence of false positives due to optical artefacts. Moreover, hydrodynamic non-ideality can be assessed by the residuals obtained from the analysis. The sedimentation coefficient distributions obtained by AC are in excellent agreement with the results from AUC. Brownian dynamics simulations were used to generate numerical sedimentation data to study the influence of diffusion on the obtained distributions. Our approach is further validated using polystyrene and silica nanoparticles. In particular, we demonstrate the strength of AC for analysing multimodal distributions by means of gold nanoparticles.

Separation of nanoparticles: Filtration and scavenging from waste incineration plants - Förster, Henning; Thajudeen, Thaseem; Funk, Christine; Peukert, Wolfgang (Waste Management, 2016)
Increased amounts of nanoparticles are applied in products of everyday life and despite material recycling efforts, at the end of their life cycle they are fed into waste incineration plants. This raises the question on the fate of nanoparticles during incineration. In terms of environmental impact the key question is how well airborne nanoparticles are removed by separation processes on their way to the bag house filters and by the existing filtration process based on pulse-jet cleanable fibrous filter media. Therefore, we investigate the scavenging and the filtration of metal nanoparticles under typical conditions in waste incineration plants. The scavenging process is investigated by a population balance model while the nanoparticle filtration experiments are realized in a filter test rig. The results show that depending on the particle sizes, in some cases nearly 80% of the nanoparticles are scavenged by fly ash particles before they reach the bag house filter. For the filtration step dust cakes with a pressure drop of 500 Pa or higher are found to be very effective in preventing nanoparticles from penetrating through the filter. Thus, regeneration of the filter must be undertaken with care in order to guarantee highly efficient collection of particles even in the lower nanometre size regime.
Keywords: Filtration efficiency; Nanoparticle scavenging; Population balance modelling; Ultrafine particle emission; Waste incineration

The effect of mixing on silver particle morphology in flow synthesis - Yang, Tao; Segets, Doris; Thajudeen, Thaseem; Han, Yongsheng; Peukert, Wolfgang (Chemical Engineering Science, 2018)
Keywords: Anisotropic silver particles; Dendrites; Analytical centrifugation; Mixing time; Plates